The World Turned Upside Down: Reaching Out to Law Libraries in Sierra Leone. (29th June 2018) - Bracey, Sarah; Simmonds, Tony
Abstract: This article, by Sarah Bracey and Tony Simmonds, explores professional and cultural challenges confronting two BIALL members involved in a project to enhance law library services in Freetown, Sierra Leone. It considers approaches to developing effectual supportive partnerships in a developing country context where the legal information ecosystem and provision of resource differ to an extent that all but inverts the familiar working world. The article traces the boundaries of what change is feasible in such a context, cautioning against over-ambition and advocating areas for future focus around staffing, co-ordination of donation programmes and digitisation of primary materials.